2014
DOI: 10.1017/s002210901400060x
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance and Innovation: Theory and Evidence

Abstract: We develop a theory to show how external and internal corporate governance mechanisms affect innovation. We predict a U-shaped relation between innovation and external takeover pressure, which arises from the interaction between expected takeover premia and private benefits of control. Using ex ante and ex post innovation measures, we find strong empirical support for the predicted relation. We exploit the variation in takeover pressure created by the passage of antitakeover laws across different states. Innov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(51 citation statements)
references
References 44 publications
1
33
0
2
Order By: Relevance
“…Our use of patenting as a proxy for innovation activities has become standard in the innovation literature (e.g., Subramanian (2009), Hsu, Tian, andXu (2014), Acharya, Baghai, and Subramanian (2013), (2014), Chava, Oettl, Subramanian, and Subramanian (2013), Sapra, Subramanian, and Subramanian (2014), and Bloom et al (2016)). Moreover, the literature has shown that patents predict economic growth, aggregate stock market value, and firm profitability (Hsu (2009), Hirshleifer, Hsu, andLi (2013), and Kogan, Papanikolaou, Seru, and Stoffman (2017)), which supports our use of patent data to examine the real effects of policy and policy uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…Our use of patenting as a proxy for innovation activities has become standard in the innovation literature (e.g., Subramanian (2009), Hsu, Tian, andXu (2014), Acharya, Baghai, and Subramanian (2013), (2014), Chava, Oettl, Subramanian, and Subramanian (2013), Sapra, Subramanian, and Subramanian (2014), and Bloom et al (2016)). Moreover, the literature has shown that patents predict economic growth, aggregate stock market value, and firm profitability (Hsu (2009), Hirshleifer, Hsu, andLi (2013), and Kogan, Papanikolaou, Seru, and Stoffman (2017)), which supports our use of patent data to examine the real effects of policy and policy uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…Sapra, Subramanian, and Subramanian (2013) develop a theoretical model and show a U-shaped relationship between innovation and takeover pressures. They also use the state-level antitakeover laws as the proxy for takeover.…”
mentioning
confidence: 99%
“…For example, Bresman et al (1999) and Bena and Li (2014) show that home investment benefits from knowledge spillovers from cross-border M&A activity. Further, M&As are found to increase productivity (e.g., Devos et al (2009)), management efficiency (e.g., Manne (1965), Wang and Xie (2009)), discipline (e.g., Sapra et al (2014), Scharfstein (1988) and innovation (e.g., Stiebale (2016)). Thus, in a mid-or long-term calculation, tax revenue losses should (at least partially) be compensated by additional tax revenue gains through increasing inbound in-vestment and increasing earnings in the residence country.…”
Section: Tax Policy Implicationsmentioning
confidence: 99%
“…Such a strong position is in the interest of a national tax policy maker due to positive spillovers of cross-border M&A activity to the MNE's residence country (e.g., Manne (1965), Scharfstein (1988), Bresman et al (1999), Devos et al (2009), Wang and Xie (2009), Bena and Li (2014), Sapra et al (2014), Stiebale (2016)). In addition, it is in a country's interest to strengthen the position of its MNEs as buyers in cross-border M&A because the range of suitable targets is limited for operational reasons (e.g., specific intellectual property that can be acquired).…”
Section: Introductionmentioning
confidence: 99%